The Irish Sea bed load parting zone: Is it a mid-sea hydrodynamic phenomenon or a geological theoretical concept?. (5th December 2021) - Creane, Shauna; O'Shea, Michael; Coughlan, Mark; Murphy, Jimmy
Abstract: On tidally-dominated shelf seas, hydrodynamic flow exerts shear stress on the seabed, inducing sediment transport and seabed evolution. Net sediment transport pathways and associated bed load partings zones (the 'head' of sediment transport pathways) are important elements of this sediment dispersal process. A robust comprehension of these dynamics on a local and regional scale are crucial for a range of offshore activities, including the rapidly growing offshore renewable energy industry. Previous studies infer a bedload parting zone (BLP) in the central Irish Sea, yet this predominantly bedform-derived BLP remains to be fully supported by underlying hydrodynamics. This study reviews how sediment transport pathways in the Irish Sea are defined to date, investigates whether a hydrodynamic regime capable of supporting this inferred BLP exists, and if proven, aims to elucidate its origin. Tidal asymmetry indicators, derived from the phase and amplitude relationships of numerically modelled M₂ and M₄ tidal constituents, reveal the existence of a symmetrical tidal zone in the proximity of the inferred BLP. New numerically modelled residual tidal current and bed shear stress vectors reinforce the presence of this distinct tidal character change and further reveal strong opposing tidal flows extending from this region, thus supporting the presence of a tidal flow capable of producing divergent bedload patterns. Analysis of tidal propagation through the Irish Sea Basin concludes that the origin of the BLP is mainly attributed to the intersection of the north and south tidal fronts at an inclined angle due to Coriolis Forcing and coastline interactions. Minor factors impacting the shape and location of the BLP are the change in tidal character at (a) abrupt bathymetry changes, (b) headlands and intricate coastline topography, and (c) large-scale constrictions. Further investigation into localised morphodynamics is needed. These findings are highly valuable to efficient marine spatial planning, underpinning a movement towards a climate resilient economy. The integrated approach used in this body of work can be applied to tidally-dominated continental shelves beyond the Irish Sea. Graphical abstract: Image 1 Highlights: Determine whether the bed load parting zone is fully supported by underlying hydrodynamics. The origin of the BLP and factors impacting its shape and location are elucidated. Strong divergence from previously defined net sediment transport pathways is revealed.